The Effect of the Flight of King Louis XVI to Varennes - Yassin, Ghufran Mohamed; Mahmoud, Amar Shaker (Journal of Ecohumanism, 2025)
France is one of the most influential and prominent European countries in the developments of events in modern European history. This research focused on the political aspect, and the subject of studying important political figures who clearly influenced the history of France is chosen, whether at the national or global level. as historical studies aim to reveal the facts that were absent from many and to understand reality better. The history of the entire world has dealt with many figures who played an important role in shaping the historical events that the countries of the world went through, including the figure of the French King Louis XVI, who is at the forefront of the prominent figures in French history during that time and what happened during his reign of the revolution The French world, the life and biography of King Louis XVI, starting from the year in which Louis XVI was born in 1754 AD, in an attempt to know how he grew up and the most important family circumstances he lived during his childhood and the nature of his relationship with his family members and his study to understand the nature of his personality, in addition to his political marriage to Marie Antoinette based on the alliance of France and Austria, until his ascension to the throne after the death of his grandfather Louis XV and his political role as King of France in the successive governments that ruled France from the year (1774 - 1793), and his reform attempts and the influence of foreign and domestic policies, in addition to the factors that led to the outbreak of the French Revolution during his reign and its development until the year 1793 AD, the year in which he was executed and the First French Republic appeared with his death.